2007
DOI: 10.1038/sj.bjp.0707157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of levosimendan on cardiac remodeling and cardiomyocyte apoptosis in hypertensive Dahl/Rapp rats

Abstract: Background and purpose: Progression of heart failure in hypertensive Dahl rats is associated with cardiac remodeling and increased cardiomyocyte apoptosis. This study was conducted to study whether treatment with a novel inotropic vasodilator compound, levosimendan, could prevent hypertension-induced cardiac remodeling and cardiomyocyte apoptosis. Experimental approach: 6-week-old salt-sensitive Dahl/Rapp rats received levosimendan (0.3 mg kg -1 and 3 mg kg -1 via drinking fluid) and high salt diet (NaCl 7%) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 46 publications
3
58
0
2
Order By: Relevance
“…[34][35][36] We showed recently that oral levosimendan ameliorated inflammatory responses, exerted antiapoptotic effects and prevented cardiomyocyte senescence in Dahl/Rapp salt-sensitive rats and in spontaneously diabetic GotoKakizaki rats with postinfarction heart failure. 17,18 Sareila et al 37 recently reported that levosimendan downregulated nuclear factor-kBdependent transcription, decreased inducible nitric oxide synthase promoter activity, inducible nitric oxide synthase expression and nitric oxide production using macrophages and fibroblasts exposed to inflammatory stimuli. Therefore, we examined cardiac MCP-1 mRNA expression in our animal model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[34][35][36] We showed recently that oral levosimendan ameliorated inflammatory responses, exerted antiapoptotic effects and prevented cardiomyocyte senescence in Dahl/Rapp salt-sensitive rats and in spontaneously diabetic GotoKakizaki rats with postinfarction heart failure. 17,18 Sareila et al 37 recently reported that levosimendan downregulated nuclear factor-kBdependent transcription, decreased inducible nitric oxide synthase promoter activity, inducible nitric oxide synthase expression and nitric oxide production using macrophages and fibroblasts exposed to inflammatory stimuli. Therefore, we examined cardiac MCP-1 mRNA expression in our animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Levosimendan (a kind gift from Orion Pharma, Espoo, Finland) was administered orally through drinking fluid to produce an approximate daily dosage of 1 mg kg À1 as in our previous rat experiments. 17,18 Fresh levosimendan solutions were prepared daily. Owing to the dipsogenic effect of Ang II, 24,25 the water intake in dTGRs is approximately three-fold higher compared with SD rats.…”
Section: Experimental Animals Blood Pressure Measurement and Samplementioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown to prevent or limit myocyte apoptosis via the activation of mitoKATP channels, a potentially protective mechanism that could be exploited for the management of acute HF (6,7).…”
Section: Introductionmentioning
confidence: 99%